1993
DOI: 10.1038/ng0793-233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the myotonic dystrophy (DM) mutation on mRNA levels of the DM gene

Abstract: Myotonic dystrophy (DM) results from the amplification of an unstable CTG repeat in the 3' untranslated region of a transcript encoding a putative serine/threonine kinase. We have analysed the amplification of the repeat and the steady state levels of the DM kinase (DMK) mRNA in tissues and cell lines from normal and congenital DM individuals. Southern blot analysis of DNA samples from a severely affected neonate shows somatic heterogeneity of the repeat in all tissues studied. RNA analyses on these tissues sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(58 citation statements)
references
References 44 publications
4
54
0
Order By: Relevance
“…This work extends the original observations of Roses and Appel linking DM to membrane protein phosphorylation (13)(14)(15) and reconfirms the role of HMPK as the active agent in DM (5,36,37). Moreover, these findings link the pathophysiology of DM (altered Na channel kinetics to the genetic abnormality) a mutation in a gene whose product has sequence similarity to protein kinases.…”
Section: Discussionsupporting
confidence: 69%
“…This work extends the original observations of Roses and Appel linking DM to membrane protein phosphorylation (13)(14)(15) and reconfirms the role of HMPK as the active agent in DM (5,36,37). Moreover, these findings link the pathophysiology of DM (altered Na channel kinetics to the genetic abnormality) a mutation in a gene whose product has sequence similarity to protein kinases.…”
Section: Discussionsupporting
confidence: 69%
“…These studies suggest that the triplet repeat expansion results in decreased steady-state levels of myotonin mRNA from the expanded allele; however, they do not distinguish between RNA stability and gene transcription. In contrast, at least one report (11) demonstrates increased abundance of myotonin mRNA in skeletal muscle from an affected individual, and the effect of the trinucleotide repeat expansion on steady-state mRNA levels remains controversial.…”
Section: Resultsmentioning
confidence: 85%
“…The general population has <37 repeats, and affected individuals have between 50 and thousands of repeats, with phenotype being correlated with expansion size (2)(3)(4)(5)(6). Lower levels of myotonin mRNA and protein have been demonstrated in patients with myotonic dystrophy (7)(8)(9)(10); however, another study described increased amounts of myotonin mRNA in tissues of an affected neonate (11). A recent study (12) demonstrated that CTG repeats created strong nucleosome positioning signals when nucleosomes were reconstituted on DNA in vitro.…”
mentioning
confidence: 99%
“…Decreased expression of steady state DMK transcript levels (9) or of mutant gene transcripts (10,11) have been reported, as well as decreased levels of a 52-55-kDa protein product in patients (9,12), consistent with a haploinsufficiency model. In contrast, we have noted mutant gene transcript expression and DMK transcript overexpression in congenital tissues (13). More recently, two studies using allelespecific quantitative reverse transcription PCR systems detected no (14) or a small (15) decrease in total DMK transcripts.…”
Section: Myotonic Dystrophy (Dm)mentioning
confidence: 93%